Chronic retroperitoneal hematoma with femoral neuropathy in a case of factor-II deficiency: an interesting case report - Kumar I., Saravana; Purushothaman, Selvaganesan M. (International Surgery Journal, 2025)
Chronic expanding hematoma is a rare condition that develops following surgery, trauma, or injury. It can occur in the retroperitoneal region after minor trauma, potentially leading to femoral neuropathy. In this case report, we present a 22-year-old male who experienced a trivial trauma during childhood, resulting in a right retroperitoneal swelling. Clinical examination revealed a swelling measuring 18×16 cm over the right lumbar and right iliac regions, which was mobile and non-tender. Central nervous system examination showed muscle atrophy in the right thigh, an absent right knee reflex, and a complete loss of sensation in the left thigh in the L2, L3, and L4 dermatomes, corresponding to femoral and obturator nerve territories. Given the patient's history of recurrent epistaxis during childhood, coagulopathy was suspected. Investigations revealed an altered coagulation profile, and the patient was diagnosed with factor II deficiency. Contrast-enhanced computed tomography (CECT) of the abdomen and pelvis and magnetic resonance imaging (MRI) with pelvic contrast suggested differential diagnoses of chronic hematoma and soft tissue sarcoma. The diagnosis was confirmed through ultrasound (US)-guided fine-needle aspiration cytology (FNAC) of the lesion. The patient underwent retroperitoneal hematoma evacuation under general anesthesia. Intraoperative findings revealed a cavity measuring 15×10 cm in the extraperitoneal plane, bordered laterally by the iliac wing, medially by a thickened peritoneal sheath, extending inferiorly to the true pelvic brim, and superiorly to the lower border of the right kidney. Postoperative recurrent bleeding was managed with fresh frozen plasma (FFP) transfusions based on a calculated formula and daily on-demand therapy. Radiological imaging confirmed complete resolution of the hematoma post-operatively. We conclude that early surgical evacuation of chronic hematomas is critical to prevent complications such as femoral neuropathy. In this patient, delayed intervention resulted in persistent femoral nerve weakness and loss of power in the affected nerve territory.